Each to Their Own: Visual Representations of Terry Pratchett’s Discworld in Time and Space - Sohár, Anikó (Imaginations)

(untitled) (York University, 2020)
When a book is translated, publishers will often modify or completely change the cover design. This paper examines the similarities and differences that result in a sample of cover designs taken from Terry Pratchett’s Discworld series. The essay analyzes these images as a form of intersemiotic translation, which prioritizes the marketing apparatus of a novel over its narrative content.